Effects of heated water-based exercise on blood pressure: a systematic review - Awassi Yuphiwa Ngomane; Raphael Martins de Abreu; Emmanuel Gomes Ciolac (Editora Champagnat, 2018)
Abstract Introduction: Systemic arterial hypertension is one of the main cardiovascular risk factors affecting several population. In this context, heated water-based exercise has emerged as a potential alternative to land- based physical exercise to reduce blood pressure (BP) in hypertensive patients. Objective: To systematically synthesize evidence for the lowering effects of heated water-based exercise on BP in a non-specific population. Methods: Scielo, Pubmed and Scopus electronic databases were searched for studies from 2005 to 2016, with the following descriptors in English: "blood pressure, exercise, immersion, blood pressure and hydrotherapy". A total of 10,461 articles were found and, after applying the inclusion and exclusion criteria, 13 articles were selected and included in the final analysis. All included articles evaluated individuals from different populations and age groups, submitted to a heated water-based exercise session and/or program. Results: The results suggest that both an acute single session and chronic training period (12 to 24 weeks) of heated water-based exercise may reduce BP in different populations (normotensive, hypertensive, postmenopausal women, and heart transplant populations). The magnitude and duration of acute and chronic hypotensive effect of exercise ranged substantially, which was probably due to the variety of exercise frequency, duration and intensity, as well as due to the studied population. Conclusion: These results suggest that heated water-based exercise may promote acute and chronic hypotensive effects in different populations. However, there is no homogeneity in the protocols used, which may have led to the heterogeneity in magnitude and duration of BP reductions.